Managerial efficiency in the perspective of time management: practice of the youth and sports general directorate of turkey - Demirel, Erkan T.; Deniz, Mehmet; Ramazanoğlu, Fikret (My University, 2007)
The efficient time management is one of the key points to gain the organizational success and obtain the competitive advantage. The performance levels of the directors in such matter have the structure affecting the general organization starting from the employees. This study was carried out to determine the approaches of the sports directors related to the efficient time management concept. The directors from the Youth and Sports General Directorate Organization were selected as the application field. When the results of research were analyzed, it was noticed that the directors remained at medium level efficiency by 60,35%, that there was meaningful difference between the efficiency levels depending on the civil status and management status variables; no meaningful difference was determined depending on the age, sex, educational level, working time and duty duration.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: time; time management; director; efficiency